Pemanfaatan Kulit Telur Sebagai Sumber CaO Untuk Katalis Pada Transesterifikasi Sawit Off Grade Menjadi Biodiesel (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Indonesia produces waste eggshell are abundant and untapped optimally. Eggshell waste as a source of CaO has the advantage that environmentally friendly, reusable and economical and thus potentially be developed as a catalyst in the reaction of biodiesel from palm fruit off grade. This research aims to produce biodiesel from low-quality raw materials and determine the effectiveness of the process by looking at the effect of process conditions such as reaction temperature, mole ratio of oil: methanol and the concentration of CaO catalyst for biodiesel yield. The process of making biodiesel is done with two stages of the reaction of esterification and transesterification reactions because the raw materials used have a free fatty acid levels are high. Processing of the data in this study conducted by response surface methodology (RSM) using Design Expert 6.0.8 program, which attack determined by central composite experimental design (CCD), which consists of three variables. Obtaining the highest biodiesel obtained as much as 88,6% under the conditions of 60Â°C reaction temperature, mole ratio of oil: methanol 1: 9 and concentration of CaO is 3 wt%. The characteristics of biodiesel produced in the form of density, kinematic viscosity, acid number and flash point are in accordance with the standards of Indonesian biodiesel. Process conditions that give real effect on the yield of biodiesel is the reaction temperature and catalyst concentration.Keywords : biodiesel, calcium oxide, response surface methodology, palm fruit off grade, transesterification.